2018
DOI: 10.1111/and.13106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ghrelin on the biochemical and histopathology parameters and spermatogenesis cycle following experimental varicocele in rat

Abstract: Ghrelin can improve the capacity of antioxidant enzymes to reduce the oxidative stress caused by varicocele and reduce spermatogenesis cycle. Therefore, special attention should be paid to ghrelin in studies evaluating antioxidant compounds in varicocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…Data from the current study showed that the body, testes, and epididymal weights were significantly lower in STZ-induced diabetic rats than the nondiabetic control group (Figures 3-6). These findings are in agreement with previous studies that also demonstrated a significant decrease in body, testicular, and epididymal weights in diabetic rats [5,18,27,28,33,45,47]. Moreover, variations in animal body and organ weights have been reported to affect spermatogenesis, sperm quality, and sperm concentration [5,18,27,28,33,45,47].…”
Section: Evaluation Of Rat Body Testicular and Epididymal Weights Ssupporting
confidence: 93%
See 4 more Smart Citations
“…Data from the current study showed that the body, testes, and epididymal weights were significantly lower in STZ-induced diabetic rats than the nondiabetic control group (Figures 3-6). These findings are in agreement with previous studies that also demonstrated a significant decrease in body, testicular, and epididymal weights in diabetic rats [5,18,27,28,33,45,47]. Moreover, variations in animal body and organ weights have been reported to affect spermatogenesis, sperm quality, and sperm concentration [5,18,27,28,33,45,47].…”
Section: Evaluation Of Rat Body Testicular and Epididymal Weights Ssupporting
confidence: 93%
“…The reduction in antioxidant enzymes has been previously reported in diabetic animals [20]. The observed reduction in antioxidant enzyme activities could be due to the oxidative inactivation of the enzyme by ROS or by the glycation of the enzymes [20,45]. The reduced activity of SOD, CAT, and GPX in the epididymal and testicular tissues has been observed following STZ induction of diabetes, and this may result in a number of deleterious effects due to the accumulation of superoxide radicals and H 2 O 2 .…”
Section: Assessment Of Antioxidant Enzymes In the Testicular And Epidmentioning
confidence: 65%
See 3 more Smart Citations